Perlindungan Indikasi Geografis terhadap Damar Mata Kucing (Shorea Javanica) sebagai Upaya Pelestarian Hutan (Studi di Kabupaten Pesisir Barat Propinsi Lampung) - Ahmad Moelyono Anasis; Mieke Yustia Ayu Ratna Sari (Fakultas Hukum Universitas Islam Indonesia, 2015)
Mata Kucing resin (Shorea Javanica) is the main commodity of Pesisir Barat Regency which is wellknown worldwide and is one of the best resin types in the world. Mata Kucing resin has the potential to be a Geographical Indication, but it has not yet been registered to the Directorate General of Intellectual Property Rights. This research discusses the obstacles why Mata Kucing resin (shorea javanica) has not been registered as a Geographical Indication and the efforts of the government of Pesisir Barat Regency to preserve Mata Kucing resin (shorea javanica) as a way of preserving its forest area. This research employed normative-empirical approach (applied law research). The conclusion based on the research finding is that neither the citizens nor government of Pesisir Barat Regency have fully understood the benefits of registering Geographical Indication so that they have not prepared any requirements to register Mata Kucing resin. The effort to preserve resin is through limiting the cutting of Mata Kucing resin trees in Lampung Province as stated in the decree of Forestry Minister Number S.459/Menhut-VI/2010.